The future of work and wellbeing: A preliminary report from a series of conversations - Kun, Andrew L.; Shaer, Orit; Sadun, Raffaella; Boyle, Linda Ng; Lee, John D. (2020)
ABSTRACT What is the future of work and wellbeing? How did the COVID-19 crisis affect this future? What can, and what should, researchers and practitioners in the field of human-computer interaction do, as they develop interfaces for work and wellbeing? These are the questions that we explore in a weekly online series of conversations with HCI experts. In this paper we share some of the insights from our first nine conversations of the series. Keywords future of work and wellbeing, attention, microtasks, post-work recovery, games, mixed reality, robots, digital assistants ABOUT THE AUTHOR/S Andrew L. Kun University of New Hampshire andrew.kun@unh.edu Andrew Kun is professor of Electrical and Computer Engineering at the U. of New Hampshire. Orit Shaer Wellesley College oshaer@wellesley.edu Orit Shaer is Class of 1966 Associate Professor of Computer Science and co-director of the Media Arts and Sciences Program at Wellesley College. Raffaella Sadun Harvard Business School rsadun@hbs.edu Raffaella Sadun is professor of Business Administration at Harvard Business School. Linda Ng Boyle University of Washington linda@uw.edu Linda Boyle is professor and chair of Industrial & Systems Engineering at the University of Washington. John D. Lee University of Wisconsin - Madison john.d.lee@wisc.edu John Lee is Emerson Electric Quality & Productivity Professor at University of Wisconsin-Madison. New Future of Work 2020, August 3–5, 2020 © 2020 Copyright held by the owner/author(s).